The Export Determinants of Indonesian Automobile in the Selected Middle-East Countries - Abi Revyansah Perwira (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
Since the automobile is one of Indonesia's high value-added commodities which has high export potency, this paper attempts to analyze and find the export determinants of Indonesian automobile in the selected Middle-east countries during the period 2006 – 2019. Those countries are chosen since they are the largest oil exporters in the world and have large GDP from it. This paper applies the gravity model and the Ordinary Least Square (OLS) regression method. Since the Fixed Effect Model (FEM) suffers from positive autocorrelation heteroscedasticity, the analysis employs Seemingly Unrelated Regression (SUR) weights on the FEM model. Based on the analysis result, the export determinants of Indonesian automobile in the selected Middle-east countries are Indonesia’s Gross Domestic Product (GDP) per capita, the importer country’s GDP per capita, economic distance between Indonesia and the importer country, exchange rate, and oil price crisis.